A method for deacidification of vegetable oil assisted by blended membrane filtration technology

By using blended membrane filtration technology in the vegetable oil deacidization process, an inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube complex solved the problems of environmental pollution and reduced oil flux, achieving an efficient and environmentally friendly vegetable oil deacidization effect.

CN118853289BActive Publication Date: 2025-03-11INNER MONGOLIA BEIFENGLING GRAIN & OIL CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410906508.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2025-03-11
Estimated Expiration
2044-07-08

AI Technical Summary

Technical Problem

In the existing vegetable oil deacidification process, alkali refining and adsorption of acid deacidification will cause environmental pollution, and the ceramic membrane is prone to blockage of water when purifying the oil-water system, reducing oil flux.

Method used

By using blended membrane filtration technology, the alkaline microcrystalline cellulose-carbon nanotube composite is loaded on an inorganic hydrophobic ceramic membrane, and its excellent adsorption properties are used to adsorb free fatty acids in the process of deacidification of vegetable oil, thereby improving the permeability and anti-pollution of the membrane.

Benefits of technology

It effectively reduces the acid price in vegetable oil, improves filtration efficiency, reduces wastewater discharge and energy consumption, avoids the production of chemically refined alkali soap feet, and retains the biologically active ingredients in the crude oil.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118853289B_ABST
    Figure CN118853289B_ABST
Patent Text Reader

Abstract

The invention discloses a method for assisting vegetable oil deacidification by using a blended membrane filtration technology, and belongs to the technical field of vegetable oil refining. The invention prepares alkaline microcrystalline cellulose by mixing potassium hydroxide and microcrystalline cellulose, crushing them, and sieving them; then, alkaline microcrystalline cellulose is mixed and cross-linked with carbon nanotubes; then, the alkaline microcrystalline cellulose-carbon nanotube complex is loaded on the surface of a ceramic membrane; finally, the alkaline microcrystalline cellulose-carbon nanotube complex is used to adsorb free fatty acids during the deacidification process of vegetable oil to reduce the acid value of crude vegetable oil, and improve the permeability and anti-pollution of the inorganic hydrophobic ceramic membrane to improve the filtration efficiency. The excellent adsorption performance of the alkaline microcrystalline cellulose-carbon nanotube complex can easily remove substances such as free fatty acids in crude vegetable oil, without the need to use chemical refining means, thereby achieving the purpose of simplifying the process and improving the oil yield. Physical filtration can retain the bioactive components and nutrients in the crude oil, thereby obtaining high-quality edible vegetable oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of vegetable oil refining, and in particular relates to a method for deacidifying vegetable oil assisted by a blended membrane filtration technology. Background Art

[0002] Deacidification is an important part of vegetable oil refining. Currently, there are several deacidification methods, including molecular distillation deacidification, alkali refining deacidification, physical refining deacidification, organic solvent extraction deacidification and supercritical fluid extraction deacidification. Among them, alkali refining deacidification is the most commonly used method in industry. This method will cause a large amount of oil loss and produce a large amount of wastewater. Molecular distillation deacidification requires high pretreatment and high equipment cost. Physical refining deacidification is not suitable for heat-sensitive oils and fats, and the cost of extraction deacidification is relatively high.

[0003] Adsorption deacidification refers to the use of solid materials that have an adsorption effect on free fatty acids to remove free fatty acids from oil. This method is low-cost, easy to operate, has no wastewater, and does not affect the environment. The key to adsorption deacidification is to use an effective adsorption deacidifier. Currently, the materials used to prepare adsorption deacidifiers are mainly rice husks and activated clay. Using these materials to prepare adsorption deacidifiers is not only complex in process, but also has "three wastes" discharged, polluting the environment.

[0004] In recent years, hydrophobic ceramic membrane separation technology has developed rapidly, and innovative technologies based on hydrophobic membranes have gradually become an important guarantee for achieving green and high-quality development. Hydrophobic organic membrane materials have been widely used in membrane processes such as oil-water separation, membrane distillation, and membrane emulsification. Patent CN113788970B discloses a carbon nanotube / microcrystalline cellulose composite membrane and its preparation method and application. The composite membrane can be used as a high-quality and efficient super-wetting filter material for the separation of water-in-oil emulsions and oil-in-water emulsions. However, organic membrane materials are often intolerant to harsh environments.

[0005] Common ceramic membrane materials are generally aluminum oxide (Al2O3), silicon oxide (SiO2), zirconium oxide (ZrO2), titanium oxide (TiO), silicon carbide (SiC) and other materials. Whether it is an oxide or non-oxide ceramic membrane, there are a large number of hydroxyl groups on the surface, which makes it naturally hydrophilic. Hydrophilic ceramic membranes purify systems with oil as the main phase and emulsified water as the impurity phase. Emulsified water is easy to form a water layer on the membrane surface and block the membrane pores, thereby greatly reducing the oil flux. Patent CN115197777A discloses a method for preparing cosmetic camellia oil based on rotating dynamic ceramic membrane filtration technology. The patent uses dynamic multi-stage filtration of ceramic membranes combined with camellia shell-based activated carbon for rapid decolorization and deodorization treatment to obtain colorless, odorless, non-toxic, high-quality cosmetic camellia oil, but its disadvantage is that it fails to effectively improve the permeability and anti-pollution properties of the membrane, and cannot improve production efficiency when facing mass production. Summary of the invention

[0006] [Technical issues]

[0007] On the one hand, in the existing vegetable oil deacidification process, alkali refining deacidification and adsorption deacidification will cause environmental pollution, molecular distillation deacidification pretreatment requirements are high and the equipment cost is high, physical refining deacidification is not suitable for heat-sensitive oils and fats, and the cost of extraction deacidification is relatively high. On the other hand, ceramic membrane purification is a system with oil as the main phase and emulsified water as the impurity phase. Emulsified water is easy to form a water layer on the membrane surface and block the membrane pores, thereby greatly reducing the oil flux.

[0008] [Technical solution]

[0009] To solve the above problems, the present invention aims to provide a method for assisting vegetable oil deacidification by using a blended membrane filtration technology, wherein an alkaline microcrystalline cellulose-carbon nanotube complex is loaded on the surface of an inorganic hydrophobic ceramic membrane by using a blended membrane filtration technology, so that it can fully adsorb free fatty acids to reduce the acid value of crude vegetable oil during the deacidification process of the vegetable oil, and effectively improve the permeability and anti-pollution properties of the inorganic hydrophobic ceramic membrane to improve the filtration efficiency. The excellent adsorption properties of the alkaline microcrystalline cellulose-carbon nanotube complex can easily remove substances such as free fatty acids in crude vegetable oil, without the need to use chemical refining methods to achieve the purpose of simplifying the process and increasing the oil yield. The use of physical filtration can retain the biologically active components and nutrients in the crude oil to a large extent, so high-quality edible vegetable oil can be obtained.

[0010] The first object of the present invention is to provide a method for deacidification of vegetable oil assisted by blended membrane filtration technology, comprising the following steps:

[0011] S1. Mixing potassium hydroxide and microcrystalline cellulose, crushing, and sieving to obtain alkaline microcrystalline cellulose;

[0012] S2, mixing and cross-linking the alkaline microcrystalline cellulose and carbon nanotubes in water to obtain a mixture;

[0013] S3, coating the mixture in step S2 on an inorganic hydrophobic ceramic membrane, and drying to obtain an inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube complex;

[0014] S4. Deacidifying the vegetable oil by using the inorganic hydrophobic ceramic membrane loaded with the alkaline microcrystalline cellulose-carbon nanotube complex in step S3.

[0015] In one embodiment of the present invention, in step S1, the mass ratio of potassium hydroxide to microcrystalline cellulose is 1:4-7, and more preferably, the mass ratio is 1:4-6.25.

[0016] In one embodiment of the present invention, in step S2, the concentration of the alkaline microcrystalline cellulose is 2-6 wt %, and more preferably, the concentration is 2-4 wt %.

[0017] In one embodiment of the present invention, in step S2, the cross-linking time of the alkaline microcrystalline cellulose and the carbon nanotubes is 6 to 10 hours, and more preferably, the cross-linking time is 6 to 8 hours.

[0018] In one embodiment of the present invention, in step S3, the loading amount of carbon nanotubes in the inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube composite is 0.75-1.75 mg / cm 2 More preferably, the loading amount is 0.75 to 1.5 mg / cm 2 .

[0019] In one embodiment of the present invention, in step S3, the drying temperature is 40-60°C, and more preferably, the drying temperature is 50-60°C.

[0020] In one embodiment of the present invention, in step S3, the drying time is 1 to 3 hours, and more preferably, the drying time is 2 to 3 hours.

[0021] In one embodiment of the present invention, in step S4, the deacidification temperature of the vegetable oil is 40-60°C, and more preferably, the deacidification temperature is 40-50°C.

[0022] In one embodiment of the present invention, in step S4, the stirring rate is 100 to 500 rpm, and more preferably, the stirring rate is 300 to 500 rpm.

[0023] In one embodiment of the present invention, the vegetable oil is one or more of peanut oil, soybean oil, rapeseed oil, sesame oil, linseed oil and olive oil.

[0024] The second object of the present invention is to provide a ceramic membrane for deacidification of vegetable oil, which is composed of a ceramic membrane, alkaline microcrystalline cellulose and carbon nanotubes; the preparation method comprises the following steps: S1, mixing potassium hydroxide and microcrystalline cellulose, crushing, and sieving to obtain alkaline microcrystalline cellulose; S2, mixing the alkaline microcrystalline cellulose and carbon nanotubes in step S1 in water and cross-linking to obtain a mixture; S3, coating the mixture in step S2 on an inorganic hydrophobic ceramic membrane, drying, and obtaining an inorganic hydrophobic ceramic membrane loaded with an alkaline microcrystalline cellulose-carbon nanotube complex.

[0025] The third object of the present invention is to request protection for the application of the above-mentioned ceramic membrane in the field of vegetable oil refining.

[0026] [Beneficial Effects]

[0027] (1) The present invention coats the alkaline microcrystalline cellulose-carbon nanotube complex on the ceramic membrane, so that it has good stability, chemical corrosion resistance and excellent recycling performance, and improves its permeability to avoid clogging, so that the penetration pressure of the oil and water phases in the hydrophobic pores is different, and efficient oil-water separation is achieved under the pore size screening effect. The modification of the alkaline microcrystalline cellulose-carbon nanotube complex increases the permeability and anti-pollution properties of the ceramic membrane, thereby improving production efficiency.

[0028] (2) The main advantage of the physical filtration of crude rapeseed oil by using an inorganic hydrophobic ceramic membrane modified with an alkaline microcrystalline cellulose-carbon nanotube composite in the present invention is that it reduces the discharge of wastewater and reduces energy consumption, while avoiding the alkali used in chemical refining, thereby preventing the production of soapstock and retaining the biologically active components in the crude oil to a large extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a schematic diagram of a method for assisting vegetable oil deacidification using a blended membrane filtration technology. DETAILED DESCRIPTION

[0030] The following is a detailed description of the specific embodiments of the present invention. It should be understood that the embodiments are intended to better explain the present invention, but are not limited to the present invention. If no specific conditions are specified in the embodiments, the conditions are carried out according to conventional conditions or manufacturer recommendations. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0031] The inorganic hydrophobic ceramic membrane is an alumina ceramic membrane with a thickness of 3 mm, a diameter of 48 mm, and a pore size of 0.2 μm, which can be purchased from Shandong Bona Biotechnology Group.

[0032] The carbon nanotube loading was calculated as follows:

[0033]

[0034] Detection method:

[0035] (1) Determination of deacidification rate:

[0036] The acid value of vegetable oil before and after deacidification is detected by titration method. The implementation standard of vegetable oil acid value is GB 5009.229-2016.

[0037] Operation steps: Mix the oil sample thoroughly and take a sample. Add ether-isopropanol mixture and phenolphthalein indicator. Shake thoroughly to dissolve the oil sample. Use 0.1 mol / L potassium hydroxide standard titration solution to neutralize the free fatty acids in the oil sample. The end point of the titration is determined by the color change of the phenolphthalein indicator. When the oil sample solution initially turns slightly red and there is no obvious fading within 15 seconds, it is the end point of the titration.

[0038] The acid value is calculated as follows:

[0039]

[0040] Where:

[0041] X AV ——acid value, in milligrams per gram (mg / g);

[0042] V——The volume of the standard titration solution consumed in the sample determination, in milliliters (mL);

[0043] V0——The volume of the standard titration solution consumed by the corresponding blank determination, in milliliters (mL);

[0044] c——the molar concentration of the standard titration solution, in moles per liter (mol / L);

[0045] 56.1 – Molar mass of potassium hydroxide in grams per mole (g / mol);

[0046] m——the weight of the oil sample, in grams (g).

[0047] The deacidification rate is calculated as follows:

[0048]

[0049] (2) Determination of membrane flux:

[0050] Measure a certain volume of crude vegetable oil and record the volume and time it takes to completely pass through the test membrane.

[0051] The membrane flux is calculated as follows:

[0052]

[0053] Example 1

[0054] A method for deacidification of vegetable oil assisted by blended membrane filtration technology comprises the following steps:

[0055] S1, potassium hydroxide and microcrystalline cellulose are mixed in a mass ratio of 1:4, and pulverized in a pulverizer at a rate of 1000 rpm for 30 seconds at room temperature, and repeated three times, and filtered through a 200-mesh filter to obtain alkaline microcrystalline cellulose;

[0056] S2, mixing the alkaline microcrystalline cellulose and carbon nanotubes in water for 10 hours to obtain a mixture, wherein the concentration of the alkaline microcrystalline cellulose is 2 wt%;

[0057] S3, coating the mixture in step S2 on an inorganic hydrophobic ceramic membrane, with a carbon nanotube loading of 1.75 mg / cm 2, dried at 40°C for 1h to obtain an inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube composite;

[0058] S4, deacidifying the rapeseed oil at 50° C. and a stirring rate of 100 rpm by passing through the inorganic hydrophobic ceramic membrane loaded with the alkaline microcrystalline cellulose-carbon nanotube complex in step S3.

[0059] Example 2

[0060] A method for deacidification of vegetable oil assisted by blended membrane filtration technology comprises the following steps:

[0061] S1, potassium hydroxide and microcrystalline cellulose are mixed in a mass ratio of 1:6.25, and pulverized in a pulverizer at a rate of 1000 rpm for 30 seconds at room temperature, and repeated three times, and filtered through a 200-mesh filter to obtain alkaline microcrystalline cellulose;

[0062] S2, mixing the alkaline microcrystalline cellulose and carbon nanotubes in water for 8 hours to obtain a mixture, wherein the concentration of the alkaline microcrystalline cellulose is 4 wt%;

[0063] S3, coating the mixture in step S2 on an inorganic hydrophobic ceramic membrane, with a carbon nanotube loading of 1.5 mg / cm 2 , dried at 50°C for 2h to obtain an inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube composite;

[0064] S4, deacidifying the rapeseed oil at 40° C. and a stirring rate of 300 rpm by passing through the inorganic hydrophobic ceramic membrane loaded with the alkaline microcrystalline cellulose-carbon nanotube complex in step S3.

[0065] Example 3

[0066] A method for deacidification of vegetable oil assisted by blended membrane filtration technology comprises the following steps:

[0067] S1, potassium hydroxide and microcrystalline cellulose are mixed in a mass ratio of 1:7, and pulverized in a pulverizer at a rate of 1000 rpm for 30 seconds at room temperature, and repeated three times, and filtered through a 200-mesh filter to obtain alkaline microcrystalline cellulose;

[0068] S2, mixing the alkaline microcrystalline cellulose and carbon nanotubes in water for 6 hours to obtain a mixture, wherein the concentration of the alkaline microcrystalline cellulose is 6 wt%;

[0069] S3, coating the mixture in step S2 on an inorganic hydrophobic ceramic membrane, with a carbon nanotube loading of 0.75 mg / cm 2 , dried at 60°C for 3h to obtain an inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube composite;

[0070] S4, deacidifying the rapeseed oil at 60° C. and a stirring rate of 500 rpm by passing through the inorganic hydrophobic ceramic membrane loaded with the alkaline microcrystalline cellulose-carbon nanotube complex in step S3.

[0071] The reaction conditions and membrane flux indicators of Examples 1 to 3 are shown in Table 1. The acid value of the crude plant oil before deacidification was 5.17 mgKOH / g, and the membrane flux of the crude plant oil before the inorganic hydrophobic ceramic membrane was optimized was 32 L / m 2 ·h.

[0072] Table 1 Reaction conditions and quality indicators of Examples 1-3

[0073]

[0074]

[0075] It can be seen from Table 1 that when the mass ratio of potassium hydroxide to microcrystalline cellulose is 1:4-7, the concentration of alkaline microcrystalline cellulose is 2-6wt%, the crosslinking time of the alkaline microcrystalline cellulose-carbon nanotube composite is 6-10h, the drying temperature is 40-60°C, the drying time is 1-3h, and the loading amount of carbon nanotubes is 0.75-1.75mg / m 2 , and combined with the subsequent refining process (deacidification temperature 40-60°C, stirring rate 100-500rpm), all can maintain good deacidification ability. And Examples 1-3 all meet the quality requirements of first-level pressed oil in rapeseed oil GB / T 1536-2021, and Example 2 is superior to Example 1 and Example 3 in terms of acid value, deacidification rate, membrane flux, etc., and has good anti-pollution ability.

[0076] Comparative Example 1

[0077] Referring to Example 2, the mass ratio of potassium hydroxide to microcrystalline cellulose was changed to 1:4, 1:7, and 1:8, and the other steps remained unchanged. The acid value, deacidification rate, and membrane flux after deacidification were measured, as shown in Table 2.

[0078] Table 2 Reaction conditions and quality indicators of Comparative Example 1 and Example 2

[0079]

[0080] As can be seen from Table 2, with the increase of the mass ratio of potassium hydroxide to microcrystalline cellulose, the acid value shows a trend of first decreasing and then increasing, and the deacidification rate and membrane flux both show a trend of first increasing and then decreasing. When the mass ratio of potassium hydroxide to microcrystalline cellulose powder is 1:6.25, the deacidification rate and membrane flux values ​​are the highest, which indicates that the alkaline microcrystalline cellulose and carbon nanotubes have good cross-linking properties at this concentration. When the mass ratio of potassium hydroxide to microcrystalline cellulose powder is 1:8, its deacidification ability is greatly reduced, which destroys the cross-linking of alkaline microcrystalline cellulose and carbon nanotubes.

[0081] Comparative Example 2

[0082] Referring to Example 2, the concentration of alkaline microcrystalline cellulose was changed to 2wt%, 6wt%, and 8wt%, and the other steps remained unchanged. The acid value, deacidification rate, and membrane flux after deacidification were measured, as shown in Table 3.

[0083] Table 3 Reaction conditions and quality indicators of Comparative Example 2 and Example 2

[0084]

[0085] As can be seen from Table 3, with the increase of alkaline microcrystalline cellulose concentration, the acid value shows a trend of first decreasing and then increasing, and the deacidification rate and membrane flux both show a trend of first increasing and then decreasing. When the alkaline microcrystalline cellulose concentration is 2wt%, its deacidification rate and membrane flux values ​​are the highest, which shows that at this concentration, alkaline microcrystalline cellulose and carbon nanotubes have good cross-linking properties. When more alkaline microcrystalline cellulose is added, it is not conducive to its cross-linking with carbon nanotubes, thereby affecting the deacidification efficiency. In addition, the modified ceramic membrane still has good anti-pollution ability.

[0086] Comparative Example 3

[0087] Referring to Example 2, the cross-linking time was changed to 4 h, 6 h, and 12 h, and the other conditions remained unchanged. The acid value, acid removal rate, and membrane flux after deacidification were measured, as shown in Table 4.

[0088] Table 4 Reaction conditions and quality indicators of Comparative Example 3 and Example 2

[0089]

[0090]

[0091] As can be seen from Table 4, with the increase of cross-linking time, the acid value shows a trend of first decreasing and then increasing, and the deacidification rate and membrane flux both show a trend of first increasing and then decreasing. When the cross-linking time is 8h, the deacidification rate and membrane flux values ​​are the highest, which shows that the alkaline microcrystalline cellulose and carbon nanotubes have good cross-linking properties at this concentration. When the cross-linking time is too short, the alkaline microcrystalline cellulose cannot be well combined with the carbon nanotubes. When the cross-linking time is too long, the cross-linking state may have been destroyed and the deacidification efficiency can no longer be increased. When the cross-linking time is too short or too long, the composite will not be completely coated on the surface of the ceramic membrane, resulting in a decrease in membrane flux.

[0092] Comparative Example 4

[0093] Referring to Example 2, the loading amount of carbon nanotubes was changed to 0.75 mg / cm 2 , 0.5mg / cm 2 , 2.5mg / cm2 The other conditions remained unchanged, and the acid value, acid removal rate and membrane flux after deacidification were measured, as shown in Table 5.

[0094] Table 5 Reaction conditions and quality indicators of Comparative Example 4 and Example 2

[0095]

[0096]

[0097] It can be seen from Table 5 that with the increase of the loading amount, the acid value shows a trend of first decreasing and then increasing, and the acid removal rate and membrane flux both show a trend of first increasing and then decreasing. 2 ·h, the deacidification rate and membrane flux are the highest, which shows that the alkaline microcrystalline cellulose-carbon nanotube composite can be well combined with the ceramic membrane under this loading amount. When the loading amount is too small, the ceramic membrane may not be completely covered. When the loading amount is too high, the ceramic membrane will be blocked and the membrane flux will be reduced, resulting in the inability to increase the deacidification efficiency.

[0098] Comparative Example 5

[0099] Referring to Example 2, the drying temperature was changed to 40°C, 60°C, and 70°C, and the other conditions remained unchanged. The acid value, acid removal rate, and membrane flux after deacidification were measured, as shown in Table 6.

[0100] Table 6 Reaction conditions and quality indicators of Comparative Example 5 and Example 2

[0101]

[0102] It can be seen from Table 6 that with the increase of drying temperature, the acid value shows a trend of first decreasing and then increasing, and the acid removal rate and membrane flux both show a trend of first increasing and then decreasing. When the drying temperature is 50°C, the acid removal rate and membrane flux values ​​are the highest, which shows that this temperature can promote the cross-linking of alkaline microcrystalline cellulose and carbon nanotubes. When the drying temperature is too low, the alkaline microcrystalline cellulose cannot be well combined with the carbon nanotubes. When the drying temperature is too high, the non-covalent bonds formed by the blending structure may be destroyed, resulting in the inability to increase the acid removal efficiency.

[0103] Comparative Example 6

[0104] Referring to Example 2, the drying time was changed to 1 h, 3 h, and 4 h, and the other conditions remained unchanged. The acid value, acid removal rate, and membrane flux after deacidification were measured, as shown in Table 7.

[0105] Table 7 Reaction conditions and quality indicators of Comparative Example 6 and Example 2

[0106]

[0107] As can be seen from Table 7, with the increase of drying time, the acid value shows a trend of first decreasing and then increasing, and the deacidification rate and membrane flux both show a trend of first increasing and then decreasing. When the drying time is 2h, the deacidification rate and membrane flux values ​​are the highest, which shows that this drying time can promote the cross-linking of alkaline microcrystalline cellulose and carbon nanotubes. When the drying time is too short, the alkaline microcrystalline cellulose cannot be well combined with the carbon nanotubes. When the drying time is too long, the non-covalent bonding of the alkaline microcrystalline cellulose-carbon nanotube complex may be destroyed, resulting in the inability to increase the deacidification efficiency.

[0108] Comparative Example 7

[0109] Referring to Example 2, the deacidification temperature in the deacidification process was changed to 50°C, 60°C, and 70°C, and the other conditions remained unchanged. The acid value, deacidification rate, and membrane flux after deacidification were measured, as shown in Table 8.

[0110] Table 8 Reaction conditions and quality indicators of Comparative Example 7 and Example 2

[0111]

[0112]

[0113] As can be seen from Table 8, with the increase of deacidification temperature, the acid value shows a trend of gradual increase, and the deacidification rate and membrane flux show a trend of gradual decrease. When the deacidification temperature is 40°C, the deacidification rate and membrane flux values ​​are the highest, which shows that this deacidification can promote the cross-linking of alkaline microcrystalline cellulose and carbon nanotubes. When the deacidification temperature is too high, it may destroy the non-covalent bonding of the alkaline microcrystalline cellulose-carbon nanotube complex, resulting in the inability to increase the deacidification efficiency and affect the membrane flux.

[0114] Comparative Example 8

[0115] Referring to Example 2, the stirring rate during the deacidification process was changed to 100 rpm, 500 rpm, and 600 rpm, and the other conditions remained unchanged. The acid value, deacidification rate, and membrane flux after deacidification were measured, as shown in Table 9.

[0116] Table 9 Reaction conditions and quality indicators of Comparative Example 8 and Example 2

[0117]

[0118] As can be seen from Table 9, with the increase of stirring rate, the acid value shows a trend of first decreasing and then increasing, and the acid removal rate and membrane flux both show a trend of first increasing and then decreasing. When the stirring rate is 300rpm, the acid removal rate and membrane flux values ​​are the highest, which shows that this stirring rate helps the crude oil to pass through the ceramic membrane. When the stirring rate is too slow, the crude oil moves slowly, resulting in a decrease in the acid removal effect. When the stirring rate is too fast, there is a binding force that affects the acid adsorption, resulting in the inability to increase the acid removal efficiency.

[0119] Comparative Example 9

[0120] Referring to Example 2, the membrane carrier was changed to polysulfone membrane, polypropylene membrane, and cellulose acetate membrane, and the other conditions remained unchanged. The acid value, deacidification rate, and membrane flux after deacidification were measured, as shown in Table 10.

[0121] Table 10 Reaction conditions and quality indicators of Comparative Example 9 and Example 2

[0122]

[0123] It can be seen from Table 10 that after changing the membrane carrier (polysulfone membrane, polypropylene membrane, cellulose acetate membrane), the deacidification rate and membrane flux are not as efficient as the ceramic membrane. This shows that the organic membrane cannot function well in this system and is not suitable for the deacidification of vegetable oils. However, the ceramic membrane shows a good deacidification rate and membrane flux in this system, which is beneficial for the deacidification process of vegetable oils and improves the membrane's anti-pollution ability.

[0124] Comparative Example 10

[0125] Referring to Example 2, some steps were omitted, and the other conditions remained unchanged. The acid value, deacidification rate and membrane flux after deacidification were measured, as shown in Table 11.

[0126] Table 11 Reaction conditions and quality indicators of Comparative Example 10 and Example 2

[0127] Reaction conditions and quality indicators Example 2 Experiment 1 Experiment 2 Whether there is alkaline microcrystalline cellulose (step S1) yes yes no Whether there are carbon nanotubes (step S2) yes no yes Whether there is a ceramic membrane carrier (step S3) yes yes yes

[0128]

[0129] It can be seen from Table 11 that when step S1 or S2 is omitted, the deacidification rate and membrane flux decrease significantly. This shows that the combination of alkaline microcrystalline cellulose, carbon nanotubes and ceramic membrane is beneficial for deacidification of vegetable oil and can significantly improve the membrane's anti-fouling ability.

[0130] In summary, when the mass ratio of potassium hydroxide to microcrystalline cellulose powder is 1:4-7, the concentration of alkaline microcrystalline cellulose is 2-6wt%, the crosslinking time of alkaline microcrystalline cellulose-carbon nanotube composite is 6-10h, and the loading amount of carbon nanotubes is 0.75-1.75mg / m 2, the drying temperature is 40-60℃, the drying time is 1-3h, and combined with the subsequent refining process (deacidification temperature 40-60℃, stirring speed 100-500rpm), it can maintain good deacidification ability. And it meets the quality requirements of first-level pressed oil in rapeseed oil GB / T1536-2021, and has good anti-pollution ability.

[0131] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for deacidification of vegetable oil assisted by blended membrane filtration technology, characterized in that: The following steps are involved: S1. Mixing potassium hydroxide and microcrystalline cellulose, crushing, and sieving to obtain alkaline microcrystalline cellulose; S2, mixing and cross-linking the alkaline microcrystalline cellulose and carbon nanotubes in water to obtain a mixture; S3, coating the mixture in step S2 on an inorganic hydrophobic ceramic membrane, and drying to obtain an inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube complex; S4, deacidifying the vegetable oil by using the inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube complex in step S3; In step S1, the mass ratio of potassium hydroxide to microcrystalline cellulose is 1:4-7; In step S2, the concentration of the alkaline microcrystalline cellulose is 2 to 6 wt %, and the cross-linking time between the alkaline microcrystalline cellulose and the carbon nanotubes is 6 to 10 hours; In step S3, the amount of carbon nanotubes loaded in the inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube composite is 0.75-1.75 mg / cm 2 ; In step S3, the drying temperature is 40-60° C., and the drying time is 1-3 hours.

2. The method according to claim 1, characterized in that In step S4, the vegetable oil deacidification temperature is 40-60° C., and the stirring rate is 100-500 rpm.

3. The method according to claim 1, characterized in that The vegetable oil is one or more of peanut oil, soybean oil, rapeseed oil, sesame oil, linseed oil and olive oil.

4. The method according to claim 1, characterized in that: The inorganic hydrophobic ceramic membrane is an alumina ceramic membrane.

5. A ceramic membrane for deacidification of vegetable oil, characterized in that: It is composed of ceramic membrane, alkaline microcrystalline cellulose and carbon nanotubes; The preparation method comprises the following steps: S1, mixing potassium hydroxide and microcrystalline cellulose, crushing, and sieving to obtain alkaline microcrystalline cellulose; S2, mixing and cross-linking the alkaline microcrystalline cellulose and carbon nanotubes in water to obtain a mixture; S3, coating the mixture in step S2 on an inorganic hydrophobic ceramic membrane, and drying to obtain an inorganic hydrophobic ceramic membrane loaded with an alkaline microcrystalline cellulose-carbon nanotube complex; In step S1, the mass ratio of potassium hydroxide to microcrystalline cellulose is 1:4-7; in step S2, the concentration of alkaline microcrystalline cellulose is 2-6wt%, and the cross-linking time of alkaline microcrystalline cellulose and carbon nanotubes is 6-10h; in step S3, the loading amount of carbon nanotubes in the inorganic hydrophobic ceramic membrane loaded with alkaline microcrystalline cellulose-carbon nanotube complex is 0.75-1.75mg / cm 2 ; In step S3, the drying temperature is 40-60°C and the drying time is 1-3h.

6. Application of the ceramic membrane according to claim 5 in the field of vegetable oil refining.

Citation Information

Patent Citations

  • A carbon nanotube / microcrystalline cellulose composite membrane, its preparation method and application

    CN113788970B

  • Method for preparing camellia oil for cosmetics based on rotary dynamic ceramic membrane filtration technology

    CN115197777A

  • Porous inorganic ceramic membrane-carbon nanotube-TiO2 photocatalyst composite material and preparation method thereof

    CN102744051A

  • Carbon nanotube / microcrystalline cellulose composite membrane as well as preparation method and application thereof

    CN113788970A